New Analytical Methods For The Estimation Of Racecadotril In Bulk And Pharmaceutical Formulations - E.VENUMADHAV; AMREEN NISHAT; T.NEEHA; P.BHARGAVI; A.SWETHA; G. DEVALA RAO (International Journal of Pharma and Bio Sciences, 2010)
Three simple and sensitive visible spectrophotometric methods (A-C) for the determination of Racecadotril in bulk and pharmaceutical formulations are described. They are based on the formation of colored species by treating with Folin-Ciocalteau (F.C) reagent under alkaline conditions (Method A, λmax: 742 nm) or 1, 10-phenanthroline (PTL) in the presence of ferric chloride (Method B, λmax: 510 nm) or 2, 2, -Bipyridine (BPN) in the presence of ferric chloride (Method C, λmax : 520 nm). These methods were extended to the analysis of pharmaceutical preparations and the results are compared with the reference method (USP).